Human Nutrition: Evaluation of a multidisciplinary didactic proposal based on enquiry and collaborative learning - Verónica González-Jaramillo (Investigações em Ensino de Ciências, 2021)
Given the health problems, conditions of malnutrition and other consequences of poor eating habits, there is an urgent need for nutrition education that reinforces students' knowledge of the processes that underlie the role of nutrition and guides them towards making right choices about adopting healthy lifestyles. The aims that guided this study were to design and evaluate a proposal for teaching human nutrition from a multidisciplinary perspective, based on inquiry and cooperative learning, directed to students from the seventh grade of an official educational institution in the city of Medellin, Colombia. A quasi-experimental design was carried out with the application of a concept association test, before and after the intervention, which was analyzed by the method of hierarchical clustering. Also, the results of the final questionnaire were compared using Student's t-Test. Both analysis techniques allowed to evaluate changes in conceptual relationships as a result of the intervention. This was an indicator that the proposal favored students' understanding of human nutrition, compared to those who followed the conventional teaching method.